Design and Build an IoT-Based 3-Phase Electric Motor Protection System - Adams, Billy; Bachri , Affan; Budi Laksono , Arief (University of Merdeka Malang, 2025)
The current condition of industries is very dependent on 3 phase electric motors as the production driver of the industry. Because using an electric motor can reduce pollution and is easy to maintain. However, 3 phase electric motors also need maintenance so that they are always ready to be used when needed 3-phase motor maintenance consists off, 3 phase electric motors are always kept clean, because if dirt gets into the 3-phase electric motor it will disrupt its performance. The control system of a 3-phase electric motor must always be maintained in good condition, if there is damage it must be replaced immediately. A protection system for the 3-phase electric motor must be provided so that the 3-phase electric motor does not experience damage that could disrupt the production process.